USE OF INFORMATION TECHNOLOGIES IN EDUCATION (Multidisciplinary Journal of Science and Technology, 2024)
This article considered the ways of effective use of information technologies in teaching young students. Based on the analysis of the regulatory legal framework, scientific and methodical literature on the studied topic, several effective methods of using modern computer technologies in education were classified.